The Global Swedes Abroad SOM Survey 2014 - SOM Institute, University of Gothenburg (University of Gothenburg, 2016)
In the autumn of 2014 the first SOM survey aimed at Swedes living abroad, was conducted. The SOM survey to expatriates focus, like the National SOM surveys, on three themes - society, public opinion and mass media. The survey was answered by 2668 people in 103 countries.
Research Director was Maria Solevid.

Purpose:

The main purpose is to examine the habits, values and opinions of Swedish expatriates.

Hösten 2014 genomfördes den första undersökningen på SOM-institutet som riktade sig till svenskar boendes utomlands. Mätningen skedde genom samverkan mellan flertalet forskningsprojekt och utfördes vid SOM-institutet, Göteborgs universitet. SOM-undersökningen till utlandssvenskar fokuserar, likt de nationella SOM-undersökningarna, på tre teman - samhälle, opinion och massmedier. Undersökningen besvarades av 2 668 personer i 103 länder.
Ansvarig undersökningsledare var Maria Solevid.

Syfte:

Huvudsyftet är att utifrån olika frågeställningar undersöka utlandssvenskarnas vanor, värderingar och åsikter.
SOM-undersökningen till utlandssvenskar 2014
Keywords: mass media; massmedia; population migration; migration; public sector; offentlig sektor; health; hälsa; social welfare; social välfärd; trust; förtroende; social welfare expenditure; utgift för social välfärd; national identity; nationell identitet; community identification; medborgaridentitet; citizenship; medborgarskap; voting; röstning; friends; vänner; political interest; politiskt intresse; political behaviour; politiskt beteende; party identification; partiidentifikation; book use; bokanvändning; television channels; tv-kanaler; languages; språk; news; nyheter; television programmes; tv-program; living abroad; utlandsbosatt; political participation; politiskt deltagande; television viewing; tv-tittande; wildlife; naturliv; religious practice; religionsutövning; language skills; språkfärdigheter; political parties; politiska partier; emigration; emigration; schools; skolor; community behaviour; samhällsdeltagande; households; hushåll; social welfare philosophy; social välfärdsfilosofi; cultural participation; kulturdeltagande; personal contact; personlig kontakt; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; languages used at home; språk som används i hemmet; radio listening; radiolyssnande; Swedish expatriates; utlandssvenskar; expatriate votes; utlandsröster; expatriate; utlandsboende; diaspora; diaspora; social media; sociala media; CORS; CORS; Migration; Migration; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap